Optical-electronic systems for new photomedical technologies - Kozhukhar, Olexander (Видавництво Львівської політехніки, 2012)
In this paper new developments of the opticalelectronic systems of the directed non-coherent radiation are offered for various branches of medicine are given.
Keywords: photomedical technologies; stimulation